Analisa Gas Terlarut Pada Minyak Transformator Daya 150 kV Dengan Menggunakan Metode Duval Pentagon - Devita Amalia; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Transformer oil is one of the important components of a transformer, because in addition to its function as an insulator which provides the function of inter-winding insulation inside the transformer, as well as the cooling medium to absorb heat from the transformer core and transformer winding. The content of gases dissolved in transformer oil indirectly indicate the condition of the transformer itself. Therefore, analysis of transformer oil or Diissolved Gas analys (DGA) needs to be done to determine the type of interference that may occur in the transformer, which can be directly carried out an action and special attention to the transformer before the condition worsens. The final task is about the maintenance actions that must be done to the results of gas content dissolved in transformer insulating oil. This research was conducted by comparing some methods of interpretation that is TDCG, Duval triangle, and Duval pentagon. The test sample used for analysis is the transformer oil samples at some substations owned by PT. PLN (Persero) P3BS UPT Pekanbaru, Riau. The results showed that increasing the amount of dissolved combustible gas in transformer oil will result in reduced performance of the transformer. This would explain that the transformer has impaired which can be disturbances thermal (thermal fault), partial discharge, or arcing.  Keywords: transformer oil, DGA, Duval method, Disruption